INJIL DAN TRADISI LOKAL: KONTEKSTUALISASI TEOLOGI DALAM PERKEMBANGAN GEREJA DI ASIA TIMUR: Pola Interaksi Ajaran Injil Dengan Sistem Kepercayaan Tradisi Lokal - halawa, fa'ahakhododo; Bambangan, Malik (Sekolah Tinggi Teologi Satyabhakti, East Java, 2025)
The present article aims to explore the contextualization of theology in thedevelopment of the church in East Asia, focusing on the interaction betweenthe teachings of the Gospel and local traditional belief systems. The approachused in this study is a qualitative method. Our findings in this study suggestthat churches in East Asia attempt to integrate fundamental Christianteachings and adapt to local cultural needs and customs. The research foundthat despite efforts to create worship that is more relevant to local cultures,churches are still careful not to mix Christian teachings with traditions thatcould undermine the core teachings of the faith. In addition, the research alsofound that there is a difficulty in finding a balance between liturgicalinnovation and maintaining the holiness of Christian teachings. Too muchadaptation to local cultural elements can lead to a loss of authentic Christianidentity, while too little adaptation can make Christianity difficult to beaccepted by society. To deal with this kind of conflict, churches in East Asiahave endeavored to develop theologies rooted in their local traditions. In thisway, churches in East Asia seek to create a deeper understanding of how thegospel can interact with the social, cultural and spiritual needs of localcommunities. One of the important findings of this study is also theimportance of active congregational participation in the contextualizationprocess. This congregational participation and diologetics help local churchesto be more sensitive to existing social and cultural dynamics, as well as makea greater contribution in determining relevant forms of worship and teaching.This includes the avoidance of practices that could lead to syncretism, i.e. themixing of Christian teachings with traditional elements that are contrary tothe Christian faith.